Assessment of nutrition knowledge among university students: a systematic review - Nawsherwan,; Haq, Ijaz ul; Tian, Qing; Ahmed, Bilal; Nisar, Muhammad; Inayat, Hafiz Zubair; Yaqoob, Areeba; Majeed, Fatima; Shah, Jahan; Ullah, Amin; Wang , Suqing (Progress in Nutrition, 2021)
Background: Nutrition knowledge is one of the influential factors which have a significant relation with chronic diseases and diet quality. This study aimed to conduct a systematic review of nutrition knowledge assessment among university students. Methods: An online article’s search was done using the PubMed search engine. Articles' search criterion included nutrition knowledge assessment related to observational studies among university going students. The article has been presented according to the PRISMA checklist. STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) criterion was used for the methodological quality of the included papers. Mann Whitney tests were used for the comparison. Results: A total of 1470 articles were retrieved, and in-depth 29 English language articles were selected. The sample size ranges from 63-1037 respondents. Most of the studies didn't report the sampling techniques. The majority of papers (75.9 %) had 50-80 % (category B) STROBE points. There was no significant difference in articles regarding nutrition knowledge published before and after 2000 (P>0.05). Conclusion: These studies reveal that over a long period researchers didn't maintain the quality of work in this particular area. The STROBE criterion should be strictly followed for observational studies for good quality work in assessing nutrition knowledge among young population.